(untitled) (Sociología y tecnociencia, 2023)
This research is motivated by the fact that currently child marriage is a form of violation of human rights and is an indicator of various other global health problems. Yemen is one of the largest contributors to child marriage cases in the Middle East and Yemen is home to 4 million child brides, and 1.4 million of it got married before the age of 15. This study aims to analyze and describe the role of UNFPA-UNICEF in the accelerate action to End Child Marriage program to reduce child marriage in Yemen in 2016-2019. This study uses qualitative research methods and uses a collection technique for collecting data of library research using secondary data collected from UNFPA and UNICEF annual reports, books, journals, articles and internet media. The results of this study show that the global implementation of the UNFPA-UNICEF program has had an impact on reducing child marriage in Yemen